2021
DOI: 10.1001/jamaneurol.2021.2004
|View full text |Cite
|
Sign up to set email alerts
|

Association Between SARS-CoV-2 Infection and Immune-Mediated Myopathy in Patients Who Have Died

Abstract: IMPORTANCE Myalgia, increased levels of creatine kinase, and persistent muscle weakness have been reported in patients with COVID-19.OBJECTIVE To study skeletal muscle and myocardial inflammation in patients with COVID-19 who had died. DESIGN, SETTING, AND PARTICIPANTSThis case-control autopsy series was conducted in a university hospital as a multidisciplinary postmortem investigation. Patients with COVID-19 or other critical illnesses who had died between March 2020 and February 2021 and on whom an autopsy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
120
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(152 citation statements)
references
References 87 publications
8
120
1
3
Order By: Relevance
“…Detection of viral load was low or negative in most skeletal and cardiac muscles and probably attributable to circulating viral RNA rather than genuine infection of myocytes. This suggests that SARS-CoV-2 may be associated with a post-infectious, immune-mediated myopathy [13]. There may be various direct and indirect mechanisms of acute myocardial injury in COVID-19 including ischemic injury, hypoxic injury (MI type 2), direct viral myocarditis, stress cardiomyopathy and systemic cytokine storm.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of viral load was low or negative in most skeletal and cardiac muscles and probably attributable to circulating viral RNA rather than genuine infection of myocytes. This suggests that SARS-CoV-2 may be associated with a post-infectious, immune-mediated myopathy [13]. There may be various direct and indirect mechanisms of acute myocardial injury in COVID-19 including ischemic injury, hypoxic injury (MI type 2), direct viral myocarditis, stress cardiomyopathy and systemic cytokine storm.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Agergaard and colleagues showed that in patients with long-term muscular complains or fatigue after mild or moderate SARS-CoV-2 infection, myopathy was a common finding ( Agergaard et al, 2021 ). Their study could not provide definite evidence for a causal link between acute infection and long-term myalgia, fatigue and myopathy but it supports the findings from the two recent autopsy studies ( Aschman et al, 2021 , Suh et al, 2021 ).…”
mentioning
confidence: 65%
“…Two recent studies investigated skeletal muscle in autopsy specimens from patients with COVID-19 ( Aschman et al, 2021 , Suh et al, 2021 ). Aschman and colleagues showed signs of muscle inflammation, ranging from mild to severe inflammatory myopathy in 60% of the patients who died with severe COVID-19, and the inflammation was more pronounced in skeletal muscle compared to cardiac muscle.…”
mentioning
confidence: 99%
“…Twenty-three patients (55%) presented overexpression of MHC-I antigens, and seven (17%) presented MHC-II overexpression; neither of these findings were observed in the autopsies performed in any of the 11 controls. 22 …”
Section: Symptoms Of Possible Muscular Originmentioning
confidence: 99%
“…Therefore, it is possible that in patients with acute and severe forms of COVID-19, muscle involvement may be explained by an exaggerated immune response (e.g., type 1 interferon overexpression or cytokine storm), or immune-mediated. 21 , 22 However, further research is needed to clarify the precise pathophysiology of the signs and symptoms suggestive of muscle damage in patients with PACS.…”
Section: Symptoms Of Possible Muscular Originmentioning
confidence: 99%